Clinical implication of 14-3-3 epsilon expression in gastric cancer - Leal, Mariana Ferreira (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate for the first time the protein and mRNA expression of 14-3-3ε in gastric carcinogenesis. METHODS: 14-3-3ε protein expression was determined by western blotting, and mRNA expression was examined by real-time quantitative RT-PCR in gastric tumors and their matched non-neoplastic gastric tissue samples. RESULTS: Authors observed a significant reduction of 14-3-3ε protein expression in gastric cancer (GC) samples compared to their matched non-neoplastic tissue. Reduced levels of 14-3-3ε were also associated with diffuse-type GC and early-onset of this pathology. Our data suggest that reduced 14-3-3ε may have a role in gastric carcinogenesis process. CONCLUSION: Our results reveal that the reduced 14-3-3ε expression in GC and investigation of 14-3-3ε interaction partners may help to elucidate the carcinogenesis process.